The Therapeutic Potential of Vitamin D in Tendinopathy: A Review of Current Evidence - Łuniewski, Bartosz; Olszanska, Monika; Macko, Angelika; Łuniewska, Maria; Nowicka, Iga Maria; Lauko, Kamil; Rafałowicz, Adam; Wojciechowska, Urszula (Quality in Sport, 2025)
Introduction: Tendinopathy refers to pathological changes in tendons that cause pain, functional impairment, and limited physical activity. These changes often result from repetitive overloading without adequate recovery, leading to microtrauma, collagen disorganization, vascular alterations, and chronic inflammation. While corticosteroids offer short-term relief, they may weaken tendon structure, and regenerative therapies like PRP and stem cells remain inconclusive. Recently, vitamin D has gained attention for its potential role in tendon healing. Low vitamin D levels are linked to higher tendinopathy risk and delayed recovery. This review aims to summarize current evidence on the role of vitamin D in tendon regeneration and its potential therapeutic application. Materials and methods: A review of selected literature in the PubMed, Scopus, Web of Science and Google Schoolar databases was conducted, using the following keywords: “Tendinopathy”, “Vitamin D”, “Tendon”. Conclusions: The potential role of vitamin D in tendon regeneration is a subject that offers novel perspectives on the treatment of tendinopathies. The therapeutic options currently available are limited in scope, frequently offering only symptomatic relief without addressing the underlying pathophysiology. The evidence from in vitro and in vivo experiments suggests that vitamin D can modulate inflammation, support collagen synthesis, and protect tenocytes from oxidative stress. Multidisciplinary management of tendinopathy should consider the assessment and correction of vitamin D deficiency, especially in older or physically active individuals. Further high-quality clinical studies are required to confirm these findings, determine optimal supplementation strategies, and evaluate long-term functional outcomes.